2019
DOI: 10.1186/s12881-018-0740-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of APOBEC3 variation in a population of HIV-1 infected individuals in northern South Africa

Abstract: BackgroundThe apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like 3 (APOBEC3) genes A3D, A3F, A3G and A3H have all been implicated in the restriction of human immunodeficiency virus type 1 (HIV-1) replication. Polymorphisms in these genes are likely to impact viral replication and fitness, contributing to viral diversity. Currently, only a few studies indicate that polymorphisms in the A3 genes may be correlated with infection risk and disease progression.MethodsTo characterize polymorphisms in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Naturally occurring non-synonymous changes in the A3G interaction domains are of clinical importance and could alter RNA binding. In this regard, Matume et al recently reported four non-synonymous polymorphisms (H186R, R256H, Q275E, and G363R) in the A3G genes in a cohort of HIV-1 infected South African individuals (Matume et al, 2019). Of these residues, only H186 is present in the A3G-NTD.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring non-synonymous changes in the A3G interaction domains are of clinical importance and could alter RNA binding. In this regard, Matume et al recently reported four non-synonymous polymorphisms (H186R, R256H, Q275E, and G363R) in the A3G genes in a cohort of HIV-1 infected South African individuals (Matume et al, 2019). Of these residues, only H186 is present in the A3G-NTD.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to an evolutionary “arms race” between hosts and viruses that has left a signature of positive selection, or rapid evolution, in host and viral genes [25]. A3s are highly polymorphic in nature, which greatly influences their viral restriction potential and cancer predisposition [2628]. There was a significant variation in rs8177832 genotype AA in healthy control and HIV-1-infected subjects in Pakistan (42.25% vs .…”
Section: Discussionmentioning
confidence: 99%
“…They are also diverse in terms of the transcripts (splice variants) they produce. The majority of variations that have been reported for APOBEC3 enzymes are at the DNA level, particularly single nucleotide polymorphisms (SNPs) [ 79 , 80 , 81 , 82 ]. Few studies have also investigated APOBEC3 splicing [ 32 , 83 , 84 , 85 ].…”
Section: Apobec3 Variationsmentioning
confidence: 99%
“…This enzyme has been suggested to play a role in HIV-1 diversification [ 37 ]. Matume et al analyzed the APOBEC3 polymorphism in 192 HIV-1-infected patients in Northern South Africa, and compared the genotype composition of this cohort with those of the HapMap, 1000 Genomes Project, and ExAC donors [ 80 ]. The study identified several variants of APOBEC3D, APOBEC3F, APOBEC3G, and APOBEC3H.…”
Section: Apobec3 Variationsmentioning
confidence: 99%